PROTOTIPE BATERAI DARI BUAH BELIMBING SAYUR SEBAGAI ENERGI ALTERNATIF - Azmi, Irham (IKIP Mataram, 2015)
This research aims to make prototype battery from star fruit as alternative energy. In everyday life electrical energy used comes from fossils that will be used up in a period of time. Therefore, it takes an alternative energy that can reduce the use of non-renewable energy. We utilize star fruit vegetable as an alternative energy used as a replacement battery, where the battery can be used as energy. Battery of star fruit has a power of 1 Volt and almost equivalent to the battery in the market that is 1.5 V voltages.